Basilar plaque on high-resolution MRI predicts progressive motor deficits after pontine infarction. Issue 1 (May 2015) - Lim, Sung-Hwan; Choi, Hojin; Kim, Hee-Tae; Kim, Juhan; Heo, Sung Hyuk; Chang, Dae-il; Lee, Ji Young; Lee, Young-Jun; Kim, Ji Young; Kim, Hyun Young; Kim, Young Seo
Abstract Background The association between progressive motor deficits (PMD) in acute pontine infarction and basilar stenosis is unclear. High resolution MRI (HRMRI) is an emerging tool for basilar artery evaluation and might provide more accurate information. We aimed to analyze the association between basilar plaque assessed by HRMRI and PMD after acute pontine infarction. Methods We identified consecutive patients with unilateral pontine infarction within 24 h of stroke onset. All the patients underwent diffusion weighted MRI, MR angiography and HRMRI within 24 h of admission. PMD was defined as an increase in National Institutes of Health Stroke Scale score by ≥ 1 during hospitalization. Factors potentially associated with PMD were validated by multivariate analyses. Results Of a total of 87 patients, 63 (72%) had paramedian pontine infarction (PPI) and PMD was observed in 28 (32%) patients. Apparent basilar plaque assessed by HRMRI was more frequent in those with PMD than in those without PMD (52% versus 33%, p < 0.001). In contrast, the frequency of basilar stenosis (>30%) assessed by MR angiography was similar regardless of PMD. In the patients with PPI, PMD was associated with hypertension and apparent plaque on HRMRI. After adjusting covariates, PMD was independently associated with apparent plaque on HRMRI (OR, 9.1; 95% CI 1.4–58.9). Conclusions Our results suggest that basilar plaque assessed by HRMRI is associated with PMD in patients with acute unilateral pontine infarction. Since basilar stenosis may be underestimated by MR angiography, HRMRI may provide additional information for predicting PMD and evaluating basilar artery stenosis.